The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1093/rheumatology/ken033
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin-3 is involved in Churg-Strauss syndrome - a serum marker closely correlating with disease activity

Abstract: This study reveals the specific association of elevated eotaxin-3 expression with high disease activity and eosinophilia in CSS patients. Eotaxin-3 might thus be a pathogenic player, biomarker and potential therapeutic target in CSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 25 publications
1
60
0
2
Order By: Relevance
“…Eosinophil depletion with anti-IL-5 monoclonal antibodies has shown promising preliminary results in treating CSS, emphasizing the mechanistic importance of IL-5 in the disorder (82). Circulating biomarkers of CSS include IL-25 and the chemokines eotaxin-3 (CCL26) and TARC (thymus and activation-regulated chemokine; also called CCL17), suggesting a potential role for these proteins in CSS pathogenesis (34,146,189,221). Several medications used in the treatment of asthma, including leukotriene modifiers, inhaled corticosteroids, and omalizumab, have been associated with the development of CSS (95,(204)(205)(206).…”
Section: Cssmentioning
confidence: 99%
“…Eosinophil depletion with anti-IL-5 monoclonal antibodies has shown promising preliminary results in treating CSS, emphasizing the mechanistic importance of IL-5 in the disorder (82). Circulating biomarkers of CSS include IL-25 and the chemokines eotaxin-3 (CCL26) and TARC (thymus and activation-regulated chemokine; also called CCL17), suggesting a potential role for these proteins in CSS pathogenesis (34,146,189,221). Several medications used in the treatment of asthma, including leukotriene modifiers, inhaled corticosteroids, and omalizumab, have been associated with the development of CSS (95,(204)(205)(206).…”
Section: Cssmentioning
confidence: 99%
“…In a recent study comparing patients with EGPA ANCA-negative and HES FIP1L1-PDGFRA-negative, none of the analyzed serum biomarkers (sIL2R, IL-5, IL-6, IL-8, IL-10, CCL17, eotaxin-1) could differentiate between the two groups of patients [80]. As previously mentioned, eotaxin-3 could differentiate active EGPA from various forms of HES, as well as from other allergic or immune diseases associated with eosinophilia [11,82].…”
Section: Hypereosinophilic Syndrome (Hes)mentioning
confidence: 90%
“…Eotaxin-3 is an eotactic chemokine that induces chemotaxis and activation of eosinophilic granulocytes in vitro, and may be involved in the pathogenesis of EGPA. Polzer, et al suggested that elevated eotaxin-3 expression was associated with high disease activity in EGPA 6 , while Dejaco, et al proposed that eotaxin-3 levels could not reliably discriminate between active and inactive disease in established EGPA 7 . In our current study, we investigated the clinical utility of eotaxin-3 as a possible biomarker of EGPA relapse.…”
Section: To the Editormentioning
confidence: 99%
“…Worsening asthma and/or rhinosinusitis without other organ involvement was not sufficient to classify a patient as having active EGPA. Serum eotaxin-3 and interleukin (IL)-6 were analyzed by ELISA (R&D Systems) 6 . Laboratory variables were compared using the Mann-Whitney U test.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation